2021
DOI: 10.1002/wcc.729
|View full text |Cite
|
Sign up to set email alerts
|

Framing “nature‐based” solutions to climate change

Abstract: In recent years, there has been a growth in scholarship on “nature‐based solutions” and “natural climate solutions” to climate change. A variety of actors have argued that these natural solutions—variously involving the protection, conservation, restoration, management, enhancement, or imitation of natural ecosystems—can play a crucial role in both mitigating and adapting to climate change. What is more, by virtue of their label, natural solutions promise to be particularly attractive to the public and policym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(45 citation statements)
references
References 70 publications
0
27
0
1
Order By: Relevance
“…Nature based solutions involving marine processes, such as CBCE restoration, are attractive not only for climate mitigation but also in the context of their other benefits, that include improved food security, reduced coastal erosion, and rebuilding marine biodiversity. They also enjoy stronger public support than ocean-based technological measures regarded as geoengineering (Bertram and Merk, 2020), although the natural/artificial distinction is arguably over-simplistic (Osaka et al, 2021). Table 1 gives estimates by different studies of the potential climatic effectiveness of CBCE restoration, considered as the additional CO 2 that might be removed and stored per year with a ramp-up time of a few years.…”
Section: Discussionmentioning
confidence: 99%
“…Nature based solutions involving marine processes, such as CBCE restoration, are attractive not only for climate mitigation but also in the context of their other benefits, that include improved food security, reduced coastal erosion, and rebuilding marine biodiversity. They also enjoy stronger public support than ocean-based technological measures regarded as geoengineering (Bertram and Merk, 2020), although the natural/artificial distinction is arguably over-simplistic (Osaka et al, 2021). Table 1 gives estimates by different studies of the potential climatic effectiveness of CBCE restoration, considered as the additional CO 2 that might be removed and stored per year with a ramp-up time of a few years.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly prominent when considering riverine/inland and coastal applications using green infrastructure strategies. Other reviews of the green infrastructure literature have found that the overlapping terminology and conceptualizations can hinder communication, collaboration, and research discovery (Kotze et al., 2020; Matsler et al., 2021; Osaka et al., 2021; Prudencio & Null, 2018). The range of terms and strategies outlined in this review highlight the fact that researchers need to clearly convey the strategies used as well as the methodologies and assumptions made to facilitate future research around green infrastructure applications.…”
Section: Discussionmentioning
confidence: 99%
“…Even in the best‐case scenarios, NbCS will contribute only a fraction of the emissions reductions necessary to limit warming to <2°C. Nonetheless, removing CO 2 from the atmosphere is part of nearly all net‐zero pathways (Rogelj et al, 2018), and NbCS may offer low‐cost mitigation along with co‐benefits such as improved air and water quality, better soil health, biodiversity maintenance (Fargione et al, 2018), and local climate adaptation (Osaka et al, 2021).…”
Section: Overviewmentioning
confidence: 99%